Spectral spherical harmonics discrete ordinate method. (January 2021) - Doicu, Adrian; Mishchenko, Michael I.; Efremenko, Dmitry S.; Trautmann, Thomas
Highlights: Radiative transfer in inhomogeneous three-dimensional media. Spectral method for solving the radiative transfer equation. Spherical harmonics discrete ordinate method. Abstract: A new method for modeling the radiative transfer in inhomogeneous three-dimensional media illuminated by a Gaussian beam is described. This approach, called the Spectral Spherical Harmonics Discrete Ordinate Method (SSHDOM), uses the Fourier expansion method to transform the three-dimensional radiative transfer into an one-dimensional equation in the spectral domain, and the Spherical Harmonics Discrete Ordinate Method (SHDOM) for its solution. Specifically, (i) the source function is represented in the spectral domain through a spherical harmonic expansion, (ii) the spectral one-dimensional radiative transfer equation is integrated along discrete ordinates through a spatial grid, and (iii) the solution method is based on the Picard iteration. Both SSHDOM and SHDOM algorithms are implemented in a common computer code.